PROCEDURAL ASPECTS OF ENSURING THE PRESERVATION OF ELECTRONIC EVIDENCE IN CRIMINAL PROCEEDINGS - Б. У. Умаров (European Science Publishing, 2024)
In the context of the digital transformation of society, electronic evidence, such as digital documents, audio and video recordings, data from mobile devices and Internet logs, are playing a key role in judicial practice. However, their unique characteristics create serious challenges related to the preservation of authenticity, admissibility and integrity of data. major problems, such as the changeability, forgery or loss of electronic evidence at the stages of its seizure, storage and presentation in court. Particular attention is paid to the legislative and technical aspects of the protection of electronic evidence, as well as the analysis of international experience in this area. It outlines procedural measures aimed at ensuring the protection of data from external interference and destruction, including the use of technologies such as digital signature, hashing, and blockchain. In addition, the issue of the need to improve national legislation, create new standards and guidelines for working with digital evidence is raised. The article emphasizes the importance of implementing legal and technical solutions to ensure the reliability of electronic evidence and offers directions for further research and improvement of the legislative framework.
Keywords: Electronic evidence, criminal procedure, preservation, authenticity, admissibility, digital data, legislation.